Electrochemical Behavior, Structure, and Morphology of Electrodeposited Nickel on Copper Alloy Prepared from Sulfate Bath without Additive Addition - Bambang Soegijono; Ferry Budhi Susetyo; Hamdan Akbar Notonegoro; Musfirah Cahaya Fajrah (Universitas Sultan Ageng Tirtayasa, 2020)
Nickel and nickel alloy has good chemical and physical properties to enhance corrosion resistance. Electrodeposited nickel layer are expected to enhance corrosion resistance of copper as substrates. The difference distance crystal plane of Nickel and Copper is about 0.02 – 0.03 Angstrom. The electrochemical behavior, structure and morphology of electrodeposited nickel on copper substrate in sulfate solution were investigated. Electrodepositions of nickel layer were conducted at room temperature with various current densities (10 mA/cm², 20 mA/cm², and 30 mA/cm²). Electrochemical behavior, structure, and morphology of the samples were analyzed by using potensiostat, x-ray diffraction (XRD), and Scanning electron microscope (SEM). The x-ray diffraction patterns show that the nickel has cubic FCC crystal system and space group Fm-3m. The current density during electrodeposition influence crystal parameter, crystallite size and micro strain of nickel film deposited. Electrodeposited nickel with current density 30 m A/cm² shows the best corrosion resistance.